Magnetoencephalographic Recordings in Infants: A Retrospective Analysis of Seizure-Focus Yield and Postsurgical Outcomes. Issue 6 (November 2018) - Garcia-Tarodo, Stephanie; Funke, Michael; Caballero, Lisa; Zhu, Liang; Shah, Manish N.; Von Allmen, Gretchen K.
Abstract : Purpose: Magnetoencephalography (MEG) is often incorporated into the presurgical work-up of children with pharmacoresistant epilepsy. There is growing literature on its role in improving selection for epilepsy surgery, particularly when brain MRI is "non-lesional" or in patients with recurrence or intractable seizures after epilepsy surgery. There are, however, no reports on the extrapolation of its role in the presurgical decision-making process of infants. Methods: We performed a retrospective analysis of infants who underwent MEG over a 10-year period at our center for presurgical work-up. We reviewed medical records to ascertain seizure history, work-up procedures including brain MRI and scalp EEG, and in the case of surgery, intracranial recordings, operative notes, and follow-up outcomes. Results: We identified 31 infants (<2 years of age) who underwent MEG recordings. Despite EEG interictal readings showing patterns of generalized dysfunction in 80%, MEG was able to pinpoint the foci of epileptic activity in 45%. In the MRI-negative group, 44% had focal lateralized interictal spikes on MEG. The sensitivity of MEG to detect interictal epileptiform activity was 90%, and its ability to provide additional information was 28%. Among 18 infants who had surgery, 13 became seizure free at follow-up. The percentage of infants with a focal spike volume on MEG studies and a seizure-free outcome was 66%. Conclusions: MEG recordings in infants were found to be as sensitive for identifying seizure focus as other age groups, also supplying additional information to the decision-making process and validating its role in the presurgical work-up of infants with intractable epilepsy.